2021
DOI: 10.3389/fphys.2021.706743
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid Antibodies From Women With Pregnancy Morbidity and Vascular Thrombosis Induce Endothelial Mitochondrial Dysfunction, mTOR Activation, and Autophagy

Abstract: Antiphospholipid syndrome (APS) is an autoimmune disease characterized by thrombosis and pregnancy morbidity (PM) obstetric events together with persistent high titers of circulating antiphospholipid antibodies (aPL). Several mechanisms that explain the development of thrombosis and PM in APS include the association of aPL with alterations in the coagulation cascade and inflammatory events. Other mechanisms disturbing cellular homeostases, such as mitochondrial dysfunction, autophagy, and cell proliferation, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 76 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…Antiphospholipid syndrome (APS) is defined as an autoimmune multisystem disease featured by the development of arterial and venous thromboembolic events and/or pathological pregnancies, mainly recurrent abortion, under the condition of persistently positive antiphospholipid antibody (aPL). [1][2][3] APS can be primary or occur in patients with systemic lupus erythematosus (SLE) or other systemic autoimmune diseases. 4 Dysregulation of immune function in APS patients produces a variety of autoantibodies, which causes thrombocytopenia while disrupting the integrity of vascular endothelial cells, leading to thrombosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antiphospholipid syndrome (APS) is defined as an autoimmune multisystem disease featured by the development of arterial and venous thromboembolic events and/or pathological pregnancies, mainly recurrent abortion, under the condition of persistently positive antiphospholipid antibody (aPL). [1][2][3] APS can be primary or occur in patients with systemic lupus erythematosus (SLE) or other systemic autoimmune diseases. 4 Dysregulation of immune function in APS patients produces a variety of autoantibodies, which causes thrombocytopenia while disrupting the integrity of vascular endothelial cells, leading to thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…Antiphospholipid syndrome (APS) is defined as an autoimmune multisystem disease featured by the development of arterial and venous thromboembolic events and/or pathological pregnancies, mainly recurrent abortion, under the condition of persistently positive antiphospholipid antibody (aPL) 1–3 . APS can be primary or occur in patients with systemic lupus erythematosus (SLE) or other systemic autoimmune diseases 4 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, non‐criteria aPL were detected using an in‐house ELISA standardized in our group based on the technique published by Kwak et al 52 . and described elsewhere 53 …”
Section: Methodsmentioning
confidence: 99%
“…Another collection of recent studies evaluated endothelial activation and dysfunction in cultured endothelial cells exposed to various serum factors from APS patients [33 ▪▪ ,34,35]. One study found that IgG isolated from patients with different disease phenotypes (primary APS, secondary APS, APS refractory to treatment, and obstetric APS) resulted in the differential expression of markers related to endothelial activation and dysfunction [33 ▪▪ ].…”
Section: Endothelial Activation and Injurymentioning
confidence: 99%
“…Another study evaluated the response of human umbilical vein endothelial cells (HUVECs) upon exposure to polyclonal IgG isolated from the serum of women with both pregnancy morbidity and vascular thrombosis [34]. HUVECs were found to have increased cellular stress, as evidenced by increased mitochondrial hyperpolarization and increased activation of the mTOR and autophagic pathways [34]. A third study showed that a complex of oxidized low-density lipoprotein/ b 2 GPI/ab 2 GPI contributes to endothelial dysfunction by inhibited autophagy via PI3K/AKT/mTOR and endothelial nitric oxide synthase-signaling pathways [35].…”
Section: Andandmentioning
confidence: 99%